Perancangan Informasi Pengolahan Mangrove Jackie Gold Melalui Media Buku - Saptaji, Hari; Cahyadi, Arif Try (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Mangroves are tropical species that usually grow and develop on coastlines and river estuaries exposed to tides. Mangroves, which are usually still seen as plants that protect beaches from seawater abrasion, are used as tourist attractions, but other uses of mangroves can also be used as ingredients for processed products. Jackie Gold is an MSME that has successfully processed mangroves into several food and beverage products. The research method used is qualitative by conducting interviews, observations, and literature studies finding that mangroves can be made into various products but are still ineffective. This is because the community does not know about mangrove-processed products. This led researchers to design information media through book media as a solution. This design aims to inform the public about mangroves which can be used as processed products. The use of books is expected to increase the understanding and knowledge of the Indramayu coastal community.